Preventive and therapeutic application of molecular hydrogen in situations with excessive production of free radicals - Slezák, J; Kura, B; Frimmel, K; Zálešák, M; Ravingerová, T; Viczenczová, C; Okruhlicová, Ľ; Tribulová, N (Physiological research, 2016)
Excessive production of oxygen free radicals has been regarded as a causative common denominator of many pathological processes in the animal kingdom. Hydroxyl and nitrosyl radicals represent the major cause of the destruction of biomolecules either by a direct reaction or by triggering a chain reaction of free radicals. Scavenging of free radicals may act preventively or therapeutically. A number of substances that preferentially react with free radicals can serve as scavengers, thus increasing the internal capacity/activity of endogenous antioxidants and protecting cells and tissues against oxidative damage. Molecular hydrogen (H(2)) reacts with strong oxidants, such as hydroxyl and nitrosyl radicals, in the cells, that enables utilization of its potential for preventive and therapeutic applications. H(2) rapidly diffuses into tissues and cells without affecting metabolic redox reactions and signaling reactive species. H(2) reduces oxidative stress also by regulating gene expression, and functions as an anti-inflammatory and anti-apoptotic agent. There is a growing body of evidence based on the results of animal experiments and clinical observations that H(2) may represent an effective antioxidant for the prevention of oxidative stress-related diseases. Application of molecular hydrogen in situations with excessive production of free radicals, in particular, hydroxyl and nitrosyl radicals is relatively simple and effective, therefore, it deserves special attention.
Keywords: Disease; oxidační stres; Reactive Oxygen Species; nemoc; reaktivní formy kyslíku; Animals; lidé; Oxidative Stress; vodík; Hydrogen; Humans; zvířata